Teaching nonscience majors about electromagnetic radiation - Shulamit Kapon (American Physical Society, 2020)
[This paper is part of the Focused Collection on Curriculum Development: Theory into Design.] We discuss the theoretical underpinnings that informed the considerations and decisions that shaped the design of a curriculum unit entitled “Electromagnetic radiation—principles, applications, and decisions”. This unit is part (45 h) of the compulsory general science requirement for the Israeli high school matriculation curriculum in science for students who choose not to major in any scientific discipline. Its goal is to develop scientific literacy rather than expertise. During the problematizing phase that preceded the design we identified two challenges presented by the formal goal of the unit and its target audience: (i) how to foster meaningful engagement on the part of diverse groups of “outsiders to science” with complex scientific content such as electromagnetic radiation, (ii) how to translate scientific and engineering findings related to a complex phenomenon such as electromagnetic radiation, which emerge within a context of specialized knowledge and vocabulary, into lay language without corrupting their meaning. The first section of this article explores these questions through a theoretical discussion of (i) relevance, personal relevance, and meaningfulness; (ii) the implications of pursuing personal relevance on the meaning ascribed to scientific literacy of nonscientists, and the ways to support its development in school; and (iii) the ways in which personal relevance comes to bear on the choice of content and explanatory means. We then illustrate how these theoretical principles and insights were translated into curriculum design.